Projeto e implementação de um sistema eletrônico auto-oscilante com controle de luminosidade para acionamento de lâmpada fluorescente - Viana, Guilherme de Almeida (2018)
This monograph deals with the design and implementation of a fluorescent lamp reactor, with luminous intensity control. The activation of the fluorescent lamp is carried out through a half-bridge inverter with resonant LCC filter whereby the switching of the semiconductor switches is performed through the self-oscillating control circuit, considering the maximum current that can flow through the filament, in view thus increasing the lamp life. The luminous intensity control is realized through an auxiliary circuit with the use of a light sensor (LDR -Light Dependent Resistor) to measure the luminosity of the environment and control the power demanded by the lamp.